The Effects of CSF Neurogranin and APOE ε4 on Cognition and Neuropathology in Mild Cognitive Impairment and Alzheimer’s Disease - Fan, Yulan; Gao, Ying; Therriault, Joseph; Luo, Jing; Ba, Maowen; Zhang, Hua; , the Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Aging Neuroscience, 2021)
Cerebrospinal fluid (CSF) measurements of neurogranin (Ng) have emerged as a promising biomarker for cognitive decline in mild cognitive impairment (MCI) and Alzheimer's disease (AD). The apolipoprotein E ε4 (APOE ε4) allele is by far the most consistent genetic risk factor for AD. However, it is not known whether the pathophysiological roles of Ng in MCI or AD are related to APOE ε4. We stratified 250 participants from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) database into cognitively normal (CN) ɛ4 negative (CN ɛ4-), CN ɛ4 positive (CN ɛ4+), MCI ɛ4 negative (MCI ɛ4-), MCI ɛ4 positive (MCI ɛ4+), AD ɛ4 negative (AD ɛ4-), and AD ɛ4 positive (AD ɛ4+). CSF Ng levels were significantly increased in APOE ε4 carriers compared to APOE ε4 non-carriers with MCI. In addition, CSF Ng identified MCI ɛ4+ versus CN ɛ4-, but not MCI ɛ4- versus CN ɛ4-. Similarly, CSF Ng negatively correlated with Mini-Mental State Examination (MMSE) scores at baseline in the MCI ɛ4+ group. Our findings support the use of CSF Ng as a biomarker of synaptic pathology for AD. We propose that the roles of CSF Ng in the pathophysiology of MCI may be related to APOE ε4.